2010
DOI: 10.1002/dvdy.22320
|View full text |Cite
|
Sign up to set email alerts
|

Progressive neurogenesis defines lateralis somatotopy

Abstract: Fishes and amphibians localize hydromechanical variations along their bodies using the lateral-line sensory system. This is possible because the spatial distribution of neuromasts is represented in the hindbrain by a somatotopic organization of the lateralis afferent neurons' central projections. The mechanisms that establish lateralis somatotopy are not known. Using BAPTI and neuronal tracing in the zebrafish, we demonstrate growth anisotropy of the posterior lateralis ganglion. We characterized a new transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Using a Gal4 enhancer trap line for rspo2 (hspGFFDMC131A) (24), we observed intense labeling in the dorsalmost neurons of the PLL ganglion (Fig. 4G), corresponding to the neurons that innervate the terminal neuromasts (25,26). Using the same transgenic combination to detect the axons of rspo2-expressing neurons, we found that at 7 dpf, shortly before the formation of the bud-neuromast ter2′, the axons innervating ter1 and ter2 express GFP (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Using a Gal4 enhancer trap line for rspo2 (hspGFFDMC131A) (24), we observed intense labeling in the dorsalmost neurons of the PLL ganglion (Fig. 4G), corresponding to the neurons that innervate the terminal neuromasts (25,26). Using the same transgenic combination to detect the axons of rspo2-expressing neurons, we found that at 7 dpf, shortly before the formation of the bud-neuromast ter2′, the axons innervating ter1 and ter2 express GFP (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…For imaging, embryos were anesthetized with Tricain (3-amino Labeling and Imaging. Single-neuron labeling was achieved through plasmid injection in fertilized eggs, as previously described (25), using a Huc:memTdTomato construct (26). Tuna embryos were simultaneously labeled for actin by phalloidin labeling and for acetylated tubulin by immunolabeling, as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…It is conceivable that this reduction reflects a specific defect in the leading afferent neurons. The leading axons that arborize extensively within the migrating primordium, and later innervate the posteriormost neuromasts (8), are extended by the earliest differentiating afferent neurons (27). A simple explanation for precocious nerve arrest would therefore be a deficit in those early neurons.…”
Section: Resultsmentioning
confidence: 99%
“…We relied on somite number, which is an accurate measure of developmental age, to asses the timing of afferent development. The earliest PLL differentiating neurons, as visualized in the Huc:kaede reporter line, can be detected around the 18-somite stage (27). We examined the presence of fluorescent cells in the PLL ganglion of 0.15 mM ret1-MO2, Huc:kaede embryos from the 18-to 20-somite stage.…”
Section: Resultsmentioning
confidence: 99%
“…Zebrafish were maintained under standardized conditions and experiments were conducted in embryos of un-determined sex in accordance with protocols approved by the Parc de Recerca Biomèdica de Barcelona's Ethical Committee of Animal Experimentation. Tg [HuC:Kaede], HGn39D, and hspGFF53A transgenic lines have been published previously (Sato et al, 2006;Faucherre et al, 2009;Pujol-Martí et al, 2010). The hspGFFDMC130A was generated by random integration of an enhancer-trap construct .…”
Section: Methodsmentioning
confidence: 99%